SAT0102 Epitope mapping for MCV peptides and subclass of anti-MCV antibodies is a useful tool for the prediction of response to B-cell directed therapy in rheumatoid arthritis. (23rd January 2014) - Naumann, L.; Bang, H.; Egerer, K.; Meyer zum Büschenfelde, D.; Lehmann, B.; Fredenhagen, G.; Bastian, H.; Wittenborn, E.; Burmester, G.-R.; Feist, E.
Abstract : Background: In patients with rheumatoid arthritis (RA), seropositivity for either rheumatoid factor or anti-CCP antibodies has been identified as a predictive marker for treatment response to rituximab (RTX) in different studies. However, it is unclear, whether analysis of fine-reactivity against certain epitopes of citrullinated antigens or immunoglobulin subclass reactivity can contribute to the prediction of treatment response to RTX. Objectives: To investigate whether reactivity patterns against epitopes of the mutated citrullinated vimentin (MCV) antigen and/or anti-MCV subclass reactivities can contribute to differentiation of responders to RTX. Methods: Fine-reactivity against MCV was investigated in anti-MCV antibody positive patients with RA (n=34) under treatment with RTX. According to EULAR response criteria, 23 patients were classified as responders by reaching remission as defined by DAS28 <2.6 or low disease activity as defined by DAS28 <3.2. Follow-up analyses of anti-MCV response were performed using 88 synthetic overlapping MCV peptides in ELISA. The peptides used contained all known modifications of vimentin by mutation and citrullination 1 . In addition, influence of RTX treatment on anti-MCV IgG, IgM and IgA antibody reactivities was investigated by ELISA. Results: At baseline or during follow-up, none of the responders showed an anti-MCV IgA antibody response. In contrast, non-responders were positive for anti-MCV IgA in 50% of the cases at baseline and showed no reduction of antibody subclass reactivities in the follow-up. Furthermore, anti-MCV antibody subclass reactivities showed that RTX-responders were characterized by a reduction of anti-MCV IgG antibody titers, and by a normalization of anti-MCV IgM titers in all initially positive cases. At baseline, subsequent responders to RTX treatment were characterized by only a minor different epitope recognition pattern compared to non-responders. Remarkably upon treatment, a reduction of the number of recognized MCV epitopes was observed in 16 out of 23 responders (69.6%) in contrast to 3 out of 11 (27.3%) non-responders in follow-up analyses. Conclusions: Responders to RTX were characterized by a restricted immunoglobulin subclass reactivity against MCV lacking IgA anti-MCV antibodies at baseline, and a reduction of anti-MCV antibody titers as well as the epitope recognition pattern under treatment. Fine-reactivity against the MCV antigen can potentially contribute as a useful marker to predict response to RTX in anti-MCV positive RA patients. References: Bang H, Egerer K, Gauliard A, Luthke K, Rudolph PE, Fredenhagen G, Berg W, Feist E, Burmester GR. Mutation and citrullination modifies vimentin to a novel autoantigen for rheumatoid arthritis. Arthritis Rheum. 2007 Jul 30;56(8):2503-2511 Disclosure of Interest: L. Naumann Grant/Research support from: Roche Pharma AG, H. Bang Employee of: Orgentec, K. Egerer: None Declared, D. Meyer zum Büschenfelde: None Declared, B. Lehmann: None Declared, G. Fredenhagen Employee of: Orgentec, H. Bastian: None Declared, E. Wittenborn Employee of: Roche Pharma AG, G.-R. Burmester: None Declared, E. Feist: None Declared